Analysis of Cadmium Chelate Solution with Various Ligands - Gao, Hong-Wen (Asian Journal of Chemistry, 2010)
Cadmium complex's stoichiometric ratio has been determined with the following ligands, eriochrome black T (EBT), ammonium purpurate (AP), acid chrome blue K (ACBK) and calcium carboxylic acid (CCA), by the updated β-correction spectrophotometry, which is more acceptable and more simple than one of other usual methods, for example molar ratio. etc. With this principle, the complex practical molar absorptivity has been first calculated, which is higher than its apparent one at its maximum absorption wavelength. The results show that the complex ratios are: Cd/EBT = 1/2, Cd/AP = 1/4, Cd/ACBK = 1/2 and Cd/CCA = 1/1, and the practical molar adsorptivity: ε520 nm = 2.72 x 104 L mol–1 cm–1 (Cd-EBT chelate), ε10 nm = 2.74 x 104 (Cd-AP chelate), ε510 nm = 3.74 x 104 (Cd- ACBK chelate) and ε550 nm = 0.77 X 104 (Cd-CCA chelate).